Residual stresses in single particle splat of metal cold spray process – numerical simulation and direct measurement - Song, Xu (2020)
This report provides the first quantitative evaluation and prediction of residual stress arising from a single particle deposition in the metal cold spray of Ti-6Al-4V. Micro-ring-core Focused Ion Beam–Digital Image Correlation (FIB-DIC) technique is employed to determine the residual stress variation experimentally, while finite element simulation with Johnson-Cook plasticity and dynamic failure model is employed to numerically predict the residual stress distribution within single particle, and they show good agreement with each other for different impact velocities. This provides a tight link between the validated description of microscopic phenomena and the ensuing macroscopic properties and processes of the deposit.